A dilation of factor k multiplies all lengths by k.
So, in your case, all lengths double. The new length is 4.
5x+2=47 subtract 2 from both sides
5x=45 divide both sides by 5
x=9
I believe the answer to this is correct and i believe he did this by adding(i think)
First, subtract both sides by 25:
x^2 - 6x = -25
Because we're completing the square, we subtract both sides by 9:
x^2 - 6x - 9 = -34
(x - 3) = 5.831 (about)
x = 8.831
Answer:
The equivalent factored form of this equation is (x² + 49)(x - 6)
Step-by-step explanation:
<em>x³ - 6x² + 49x - 294</em>
First, group the first and second terms together and group the last two terms together.
<em>(x³ - 6x²) + (49x - 294)</em>
Find the greatest common factor of both parentheses and factor them.
x²(x - 6) + 49(x - 6)
Now, since the two terms in the parentheses are the same, then we have factored the equation correctly.
So, the factored form of the equation is (x² + 49)(x - 6)